Liberal Feminism: from Biblical Tradition to the Emergence of CEDAW - Abdullah Muslich Rizal Maulana; Farhah Farhah; Yuangga Kurnia Yahya; Naila Asy Syifa (UIN Sunan Gunung Djati Bandung, 2021)
: Liberal Feminism is an ideology that advocates for equal opportunities for men and women in a variety of areas, including employment, health, education, marriage, and family life, as well as public life and politics. Ideologically, Liberal Feminism emerged from the belief that Biblical Tradition, as documented in its verses, set women apart from men. This study would look at the connection between Biblical culture dominating women's positions in Western civilization and the advent of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). The investigation would include the patriarchal ideology found in Biblical Tradition, the notion of gender emancipation. In order to answer this research question, this research will use the method of ‘Discourse Analysis' to address the roots of Liberal Feminism as they are found in the Biblical Tradition and the method of ‘Document Analysis' to elaborate on CEDAW records. This study concludes that there is a strong connection between Biblical values and the concept of Liberal Feminism as it is embodied in CEDAW.